Assessment of the stress relaxation characteristics of critical gels formed under unidirectional shear flow by controlled stress parallel superposition rheometry - Daniel Curtis (Journal of Non-Newtonian Fluid Mechanics, 2015)
Processes involving a unidirectional shear flow component are widespread in industrial manufacturing techniques such as printing and coating, or in physiological events such as blood coagulation. Standard rheometric techniques are usually employed under quiescent conditions and as such are inappropriate for the study of microstructural modification induced by the presence of a unidirectional shear flow. We demonstrate how controlled stress parallel superposition (CSPS) may be exploited to enable accurate detection of the Gel Point and analysis of Gel Point parameters for systems undergoing a viscoelastic liquid (VEL) to viscoelastic solid (VES) transition in the presence of a unidirectional flow field. Specifically, we note that certain features of the CSPS experiment, when performed near the Gel Point, may obviate previously reported concerns regarding the experiment. A biopolymer system (gelatin) which forms gels by thermoreversible gelation is employed as a model gelling material to confirm the ability of CSPS to characterise the stress relaxation characteristics of critical-gels in the presence of a) progressively decreasing and b) progressively increasing unidirectional strain rate and oscillatory strain amplitude. Additional validation of CSPS results is reported for a silicone dielectric gel used in the industrial production of printed electronic products. Finally, CSPS is used to investigate microstructural modification of fibrin-thrombin gels as a consequence of clot formation under a unidirectional shear stress. The results confirm the validity of the CSPS technique in gelation studies and the technique is used, for the first time, to directly record the thermally induced VES to VEL transition in aqueous gelatin systems.